The new governance mechanisms for improving public service in local communities in Algeria - Elhadj, Mettai; Noureddine, Zahoufi; Ilimi, Chihab (The International tax journal, 2025)
This study aims to determine the extent to which governance mechanisms contribute to improving public service in local communities and eliminating administrative bureaucracy. This is achieved by adopting modern work methods, leveraging information and communication technology (ICT), applying modern technologies to deliver public services, and involving civil society in administrative decision-making and strategic planning to deliver public services that meet citizens' aspirations. By adopting a deductive approach using descriptive and analytical tools, this study concluded that the implementation of governance mechanisms in local communities has effectively contributed to improving public services and eliminating administrative bureaucracy. The study recommended investing in human resources by attracting qualified personnel and training workers.